Management of Primary Retroperitoneal Sarcoma (RPS) in the adult: a consensus approach from the Trans-Atlantic RPS Working Group - Bonvalot, Sylvie; Hohenberger, Peter (Annals of surgical oncology, 2015)
Background: Retroperitoneal soft tissue sarcomas (RPS) are rare tumors that include several well-defined histologic subtypes. Although surgery is the mainstay of curative therapy, no universally accepted recommendations concerning the best management have been developed to date. Optimization of the initial approach is critical for maximizing patient outcomes. Methods: An RPS Trans-Atlantic Working Group was established in 2013. The primary aim was to evaluate the current evidence critically and to develop a consensus document on the approach to this difficult disease. The outcome applies to primary RPS that is nonvisceral in origin. The evaluation included sarcomas of major veins (inferior vena cava, renal vein, ovarian/testicular vein), undifferentiated pleomorphic sarcoma of the psoas, and ureteric leiomyosarcoma (LMS). It excluded desmoid, lipoma and angiomyolipoma, gastrointestinal stromal tumors, visceral sarcomas such as those arising from the gut or its mesentery, uterine LMS, prostatic sarcoma, paratesticular/spermatic cord sarcoma, Ewing’s sarcoma, alveolar/embryonal rhabdomyosarcoma, primitive peripheral neuro-ectodermal tumor, sarcoma arising from teratoma, carcinosarcoma, sarcomatoid carcinoma, clear cell sarcoma, radiation-induced sarcoma, paraganglioma, and malignant pheochromocytoma. Results: Management of RPS was evaluated from diagnosis to follow-up, and a level of evidence was attributed to each statement. This rare and complex malignancy is best managed by an experienced multidisciplinary team in a specialized referral center. The best chance of cure is at the time of primary presentation, and an individualized management plan should be made based on the statements included in this article. Conclusions: International collaboration is critical for adding to the current knowledge. A prospective registry will be set up.